2011
DOI: 10.1007/s10812-011-9421-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of branched oligophenylene by absorption and fluorescence spectra

Abstract: A branched oligophenylene has been synthesized based on 1,3,5-tri(4′-bromophenyl)benzene. Absorption and fluorescence spectra were studied and fluorescence quantum yields and lifetimes were measured for the compound in solution. It is demonstrated that the absorption spectrum is a superposition of p-quaterphenyl, p-terphenyl, and biphenyl chromophore absorption bands in a 1:2:1 ratio. The oligomer fluorescence spectrum is found to depend on the excitation wavelength. It is shown that the oligomer fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The absorption and fluorescence properties were reported in these studies but the relationship of these properties to the molecular structures of the prepared oligomers was not examined. Recently we prepared the branched oligophenylene OPh4-1 and analyzed its structure and spectral and luminescent properties [11]. It was shown that the absorption spectrum was composed of bands from the chromophores p-quaterphenyl (PQP), p-terphenyl (PTP), and diphenyl (DP) (in ~1:2:1 ratio).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The absorption and fluorescence properties were reported in these studies but the relationship of these properties to the molecular structures of the prepared oligomers was not examined. Recently we prepared the branched oligophenylene OPh4-1 and analyzed its structure and spectral and luminescent properties [11]. It was shown that the absorption spectrum was composed of bands from the chromophores p-quaterphenyl (PQP), p-terphenyl (PTP), and diphenyl (DP) (in ~1:2:1 ratio).…”
mentioning
confidence: 99%
“…It was found that two optical centers were responsible for the fluorescence of OPh4-1. An anomalous fluorescent unit, p-hexaphenyl, was observed at a negligibly low concentration in the oligomer.Herein we continue spectral investigations of fluorescent oligophenylenes [11]. Three branched oligomers containing different p-phenyl chromophores (m = 2, 3, 4) and two fluorenylphenylene oligomers, the chromophores of which contain a conjugated chain of seven benzene rings, were prepared:…”
mentioning
confidence: 99%
See 2 more Smart Citations